Numerical simulation of non-thermal food preservation - Rauh, Cornelia; Krauß, Jens; Ertunc, Özgür; Delgado, Antonio (AIP Conference Proceedings, 2010)
Food preservation is an important process step in food technology regarding product safety and product quality. Novel preservation techniques are currently developed, that aim at improved sensory and nutritional value but comparable safety than in conventional thermal preservation techniques. These novel non-thermal food preservation techniques are based for example on high pressures up to one GPa or pulsed electric fields. in literature studies the high potential of high pressures (HP) and of pulsed electric fields (PEF) is shown due to their high retention of valuable food components as vitamins and flavour and selective inactivation of spoiling enzymes and microorganisms. for the design of preservation processes based on the non-thermal techniques it is crucial to predict the effect of high pressure and pulsed electric fields on the food components and on the spoiling enzymes and microorganisms locally and time-dependent in the treated product. Homogenous process conditions (especially of temperature fields in HP and PEF processing and of electric fields in PEF) are aimed at to avoid the need of over-processing and the connected quality loss and to minimize safety risks due to under-processing. the present contribution presents numerical simulations of thermofluiddynamical phenomena inside of high pressure autoclaves and pulsed electric field treatment chambers. in PEF processing additionally the electric fields are considered. Implementing kinetics of occurring (bio-) chemical reactions in the numerical simulations of the temperature, flow and electric fields enables the evaluation of the process homogeneity and efficiency connected to different process parameters of the preservation techniques. Suggestions to achieve safe and high quality products are concluded out of the numerical results. © 2010 American Institute of Physics.
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.numeri_29
Keywords: High Pressure Processing; Numerical Simulation; Process Design; Homogeneity; Pulsed Electric Field Processing